Detrimental Changes in Health during Menopause: The Role of Physical Activity - Hulteen, Ryan M.; Marlatt, Kara L.; Allerton, Timothy D.; Lovre, Dragana (International Journal of Sports Medicine, 2023)
Midlife women experience changes in cardiometabolic, physical, and psychosocial health during menopause that negatively impacts their overall quality of life. Factors that contribute to these increases in cardiometabolic risk include weight gain as well as increases in fat mass (particularly abdominal adiposity), insulin resistance, and vascular dysfunction. Other deleterious changes in physical health (e. g. reduced sleep health, bone density, and balance) as well as changes in psychosocial health (e. g. mood, anxiety, and depression) often coincide and are linked to these increases in cardiometabolic risk. Physical activity and exercise are important lifestyle components that have been demonstrated to improve cardiometabolic, physical, and psychosocial health, yet physical activity and exercise is known to decline during perimenopause and into the postmenopausal years. In this narrative review, we summarize these changes in overall health during menopause as well as how declining physical activity contributes to these changes. Additionally, we discuss how incorporating physical activity and exercise during menopause can potentially ameliorate health declines. We conclude that there exists a significant, positive impact of physical activity on cardiometabolic, physical, and psychological health among midlife women, particularly if undertaken during the perimenopausal and postmenopausal years.
Keywords: menopause; physical activity; exercise; metabolism; adiposity; insulin resistance